Development of novel biocompatible and biodegradable probes for photoacoustic imaging - Chan, Wilson Chin Weng (2014)
Photoacoustic imaging has recently emerged as a powerful molecular imaging modality, which provides highly specific molecular imaging with up to a few cm depth and 20-200 μm resolution, offering great potential in overcoming the limitations of other currently available imaging modalities (e.g. fluorescence imaging, nuclear imaging and magnetic resonance imaging). Current photoacoustic contrast agents, such as carbon nanotubes, gold nanorods and NIR dyes are not specifically designed for photoacoustic imaging and have limitations in terms of non-biodegradability or cytotoxicity.